2022
DOI: 10.2147/jhc.s283840
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Metabolic Syndrome as a Risk Factor for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) and metabolic syndrome (MetS) have a rising prevalence worldwide. The relationship between these two entities has long been studied and understanding it has become a public health and clinical priority. This association follows, in most patients, the path through non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), cirrhosis and finally HCC. Nonetheless, increasing evidence has been found, that shows MetS as an independent risk factor for the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…A previous study has revealed that metformin treatment can inhibit HCC cell proliferation and decrease the risk of HCC development in T2DM patients ( 22 ). We also found that metformin not only can prolong the OS but also can decrease the recurrence rate for these patients ( 23 ). Furthermore, metformin can inhibit energetic metabolism including blood glucose, which may influence the proliferation and migration of HCC cells ( 24 ).…”
Section: Discussionmentioning
confidence: 64%
“…A previous study has revealed that metformin treatment can inhibit HCC cell proliferation and decrease the risk of HCC development in T2DM patients ( 22 ). We also found that metformin not only can prolong the OS but also can decrease the recurrence rate for these patients ( 23 ). Furthermore, metformin can inhibit energetic metabolism including blood glucose, which may influence the proliferation and migration of HCC cells ( 24 ).…”
Section: Discussionmentioning
confidence: 64%
“…Serum ApoB and ApoA1 decreased in CHB, HBV-associated LC, and HBV-associated HCC groups compared with healthy controls, while there were few comparative studies between the groups 21,37,38 . HBV can modulate ApoA1 function through HBx, leading to ApoA1 dysfunction (e.g., decreased self-association ability, elevated carbonyl levels, as well as impaired lipid binding ability 20,21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and obesity are also risk factors of HCC in NAFLD patients. 107,108 The presence of type 2 diabetes and metabolic syndrome along with diabetes increases the risk of HCC 2-fold and 5-fold, respectively, while obesity (body mass index [BMI] >30 kg/ m 2 ) and severe obesity (BMI >35 kg/m 2 ) can increase the risk of HCC 2-fold and 4-fold, respectively. 100 Inflamed visceral adipose tissue induced by obesity secretes pro-inflammatory adipocytokines such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), thereby promoting systemic inflammation and insulin resistance, further exacerbating NAFLD.…”
Section: Nafldmentioning
confidence: 99%